2019
DOI: 10.22159/ajpcr.2019.v12i2.29684
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antiamebic Studies of Tamarindus Indica of Leaves Extract

Abstract: Objective: The present study deals with preliminary phytochemical screening of Tamarindus indica extracts and investigates its antiamebic effect against Entamoeba histolytica in vitro. Methods: E. histolytica was isolated from stools of patients with amebic dysentery and cultivated in lock-egg medium. The leaves extract was added to check its antiamebic activity. Results: The phytochemical screening shows that T. indica contains alkaloids, flavonoids, phenol, and tannins. T. indica extracts (aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…18 Moreover, the increase in MCHC may be due to that the RBC is fragile or destroyed, or because of the present of some immature RBC into blood circulation which may cause an increase in MCHC values. This agrees with Kotepui et al 19 and Mehdi et al 6 they found that E. histolytica-infection rats it has an effect on Hb, MCV and MCH values.…”
Section: Effect Of R Sphenocleoides Leaves Extracts On Haematological Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…18 Moreover, the increase in MCHC may be due to that the RBC is fragile or destroyed, or because of the present of some immature RBC into blood circulation which may cause an increase in MCHC values. This agrees with Kotepui et al 19 and Mehdi et al 6 they found that E. histolytica-infection rats it has an effect on Hb, MCV and MCH values.…”
Section: Effect Of R Sphenocleoides Leaves Extracts On Haematological Parameterssupporting
confidence: 91%
“…5 Also, the incidence infection of these parasites can lead to low birth weight, reduced productivity in adulthood, stunted growth, reduced hemoglobin concentration and iron level in the blood which leads to anemia. 6 World health organization reported that infect 10% of the world's population, up to 50 million cases of invasive amoebiasis and it is responsible for 100,000 deaths per year worldwide it ranks third among parasitic diseases that result to death worldwide; if not in second to malaria as a protozoan cause of death. 7 The disease is prevalent worldwide, but the highest prevalence rates have been recorded in developing countries, Indian sub-regions, parts of Central and Southern America and tropical regions of Africa.…”
Section: Introductionmentioning
confidence: 99%
“…indica is found in Asia continent, Indian subcontinent and Africa continent also, it is found in high places up to 500 m that is from Burma to Afghanistan, also in woodlands and the arid and semiarid zones up to 47°C [9]. Tamarind has an assortment of the pharmacological action, and it utilized as a part of phytomedicine around the globe for its treating diarrhea [10], antiparasitic such as Eisonia fatida, Pheretima posthuma, Ascaridia galli, Taenia solium, and Entamoeba histolytica [11][12][13], Echinococcus granulosus [14], antibacterial, antifungal [15], antidiabetic and anticancer activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Higher plants are sources of bioactive compounds continue to play a dominant role in the maintenance of human health. Reports available on the green plants to represent a reservoir of effective chemotherapeutics, which are non-phytotoxic, more systemic and easily biodegradable [11,12]. Plants are rich source of secondary metabolites with interesting biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of Ethanolic Extract: Harborne method 6 was used to prepare ethanol extract by weighing 40 grams of dry plant powder, and 400 ml of ethanol were placed in extraction thimbles which were placed in a chamber of the Soxhlet apparatus at a temperature of 50-55 °C and extraction was continuous and carried out until the color disappeared. Then, the extract was transformed into Rotary evaporator.…”
Section: Preparation Of Extractsmentioning
confidence: 99%